2007
DOI: 10.1086/522177
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of dupA in Helicobacter pylori Is Not Significantly Associated with Duodenal Ulceration in Belgium, South Africa, China, or North America

Abstract: A previous study suggested that Helicobacter pylori strains possessing dupA are positively associated with duodenal ulceration and negatively associated with gastric adenocarcinoma. We determined the prevalence of dupA in H. pylori strains recovered from 4 independent populations and found a significant association with gastric cancer but not with duodenal ulceration.Helicobacter pylori infects approximately one-half of the world's population and is a major cause of peptic ulceration and gastric adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 11 publications
8
82
2
3
Order By: Relevance
“…Our results showed a 2.4-fold increased risk of peptic ulcer (95% CI: 0.483-11.93), compared with gastritis in the infected patients who had dupA positive strains; however, this association was not statistically significant. There are other controversial results for the noted association between gastrointestinal disorders and dupA status (Lu et al, 2005;Arachchi et al, 2007;Argent et al, 2007;Nguyen et al, 2010). Although an increased risk of DU was detected in our study, the lack of significance difference in these patients could be explained by the probable lack in the function of DupA or its secretion in the responsible strains (Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a 2.4-fold increased risk of peptic ulcer (95% CI: 0.483-11.93), compared with gastritis in the infected patients who had dupA positive strains; however, this association was not statistically significant. There are other controversial results for the noted association between gastrointestinal disorders and dupA status (Lu et al, 2005;Arachchi et al, 2007;Argent et al, 2007;Nguyen et al, 2010). Although an increased risk of DU was detected in our study, the lack of significance difference in these patients could be explained by the probable lack in the function of DupA or its secretion in the responsible strains (Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Lu et al [25] and Argent et al [26] reported that the expression of the duodenal ulcer-promoting gene A (dupA) may be associated with an increased risk of duodenal ulcer and a reduced risk of gastric cancer, because the pathogenic mechanism of dupA appears to involve the induction of high interleukin (IL)-8 production in the antrum, leading to antrum-predominant gastritis, a well- recognized characteristic of duodenal ulcer. However, Hussein [1] reported that dupA promotes duodenal ulceration in some populations and gastric ulcer and gastric cancer in others, and Argent et al [26], Nguyen et al [27], and Arachchi et al [28] indicated that about 40% of H. pylori-infected patients with duodenal ulcer do not have the dupA gene, so that they required further investigation into the effects of the dupA gene.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
“…However, Hussein [1] reported that dupA promotes duodenal ulceration in some populations and gastric ulcer and gastric cancer in others, and Argent et al [26], Nguyen et al [27], and Arachchi et al [28] indicated that about 40% of H. pylori-infected patients with duodenal ulcer do not have the dupA gene, so that they required further investigation into the effects of the dupA gene. However, recently, Jung et al [29] have reported that, although cagA status was associated with inflammation and atrophy both in the antrum and in the corpus, homB (one of the hom family of H. pylori outer-membrane proteins) status was associated with inflammation and atrophy only in the corpus, so that homB gene status may be used as a factor for discriminating between the risk of gastric cancer and that of duodenal ulcer.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
“…The jhp0917 gene encodes a protein of 475 amino acids, but lacks a region homologous to the Cterminus of virB4, while jhp0918 gene encodes a product of 140 amino acids that is homologous to the missing virB4 region [51]. Since its discovery, dupA gene has been studied by various authors, and the results of their researches suggest that, in some places, dupA gene is not associated with an specific disease [52], or it is suggested that it can be associated with gastric cancer development [53][54][55], or it is directly associated with the development of duodenal ulcer disease [50,56]. Considering all these results, it is suggested that there must be diversity in gene content that can contribute to bacterial adaptation to genetically different ethnic groups that make up de human population [57].…”
Section: Virulence Factors Of H Pylorimentioning
confidence: 99%